Recasting State Reform to Ensure Resilience in an Unpredictable World - de Lancer Julnes, Patria (Revista del CLAD Reforma y Democracia, 2022)
The COVID-19 pandemic challenged the common belief that government institutions are incapable of adaptating. But it also reveals that, despite substantial gains in poverty reduction since the 1990s and countless versions of “state reform”, the Latin America and Caribbean region remains in crisis. This presentation will address the need to “recast” state reform to build resilient communities. It focuses on the need to rethink the effort to implement the 2030 Agenda, as well as the contributions of evidence-based decision-making systems. Given the desire for citizens to play an influential role in governance and state reform, three conditions are discussed that would make citizen participation and engagement prevalent. Finally, it argues for engaging universities as engines of growth and development in support of effective institutions and sustainable communities.